2017
DOI: 10.1089/dia.2017.0028
|View full text |Cite
|
Sign up to set email alerts
|

The Durability of Basal Insulin Affects Day-to-Day Glycemic Variability Assessed by Continuous Glucose Monitoring in Type 2 Diabetes Patients: A Randomized Crossover Trial

Abstract: Compared with glargine U100 treatment, glargine U300 treatment improved the MODD as assessed by CGM in type 2 diabetes patients. These findings suggest that the durability of basal insulin may be associated with day-to-day glycemic variability in type 2 diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It is assumed that 3 to 4 days are needed to achieve steady state conditions for insulin glargine U300 . Iuchi et al showed reduced glycaemic variability when comparing insulin glargine U300 and insulin glargine U100 after a 4‐week titration period (CV, 26.8% vs 25.3%) . In our study, CV was 36.1% on Day 1 compared to 31.4% on Day 4 and 28.9% on Day 7 of titration, thus showing comparable glycaemic variability for insulin glargine U300 even early in the titration phase.…”
Section: Discussionsupporting
confidence: 60%
“…It is assumed that 3 to 4 days are needed to achieve steady state conditions for insulin glargine U300 . Iuchi et al showed reduced glycaemic variability when comparing insulin glargine U300 and insulin glargine U100 after a 4‐week titration period (CV, 26.8% vs 25.3%) . In our study, CV was 36.1% on Day 1 compared to 31.4% on Day 4 and 28.9% on Day 7 of titration, thus showing comparable glycaemic variability for insulin glargine U300 even early in the titration phase.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, we have also routinely observed intermediate-term GV caused by differences in the duration of drug actions due to differences in half-life and other factors. We also reported such differences in our clinical trials using insulin [ 36 ]. Intermediate-term GV is also useful in determining the effects of the duration of action of medications and other factors.…”
Section: Intermediate-term Glycemic Variabilitymentioning
confidence: 82%
“…It has been reported that IGlar U300 is as effective for glycemic control as IGlar U100 and superior in reducing hypoglycemia according to phase 3 clinical trials performed as multi-center, open-label, and parallel-group studies [ 3–13 ]. The daily blood glucose variability assessed using continuous glucose monitoring (CGM) system was also improved by IGlar 300 treatment compared with IGlar 100 in patients with types 1 [ 17 ] and 2 diabetes [ 18 ]. Because IGlar biosimilar has an identical amino acid sequence and the same pharmaceutical form as IGlar [ 1 ], both IGlar biosimilar and IGlar U100 demonstrated similar glucose control with similar safety profiles in patients with types 1 and 2 diabetes [ 19–21 ].…”
Section: Discussionmentioning
confidence: 99%